Modern physics - Felder, Gary N.; Felder, Kenny M. (Cambridge: Cambridge University Press, 2023)
"Modern Physics intertwines active learning pedagogy with the material typically covered in an introductory survey, from the basics of relativity and quantum mechanics through recent developments in particle physics and cosmology. The flexible approach taken by the authors allows instructors to easily incorporate as much or as little active learning into their teaching as they choose. Chapters are enhanced by 'Discovery' and 'Active Reading' exercises to guide students through key ideas before or during class, while 'ConcepTests' help check student understanding and stimulate classroom discussions. Each chapter also includes extensive assessment material, with a range of basic comprehension questions, drill and practice calculations, computer-based problems, and explorations of advanced applications. A test bank and interactive animations as well as other support for instructors and students are available online. Students are engaged by an accessible and lively writing style, thorough explanations, 'Math Interludes' which account for varying levels of skill and experience, and advanced topics to further pique their interest in physics"--
Includes bibliographical references and index.
Keywords: Physics -- Textbooks; SCIENCE -- General Physics